Alles wat u moet weten over aids en andere seksueel overdraagbare aandoeningen - Coutinho, R.A.; Schalm, S.W.; Springer, M.P. (Amsterdam : Teleboek, 1988)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie